The assault on reason - Gore, Albert, 1948-; Patton, Will. (New York : Penguin Books, 2007)
Al Gore explains politics and why the American people need to be more aware of what is happening in the government.
Compact discs.
Unabridged.
Read by Will Patton.
Keywords: Bush, George W. -- 1946-; Bush, George W. -- 1946- -- Friends and associates; Audiobooks; Political culture -- United States; Democracy -- United States; Reason -- Social aspects -- United States; Reason -- Political aspects -- United States; Fear -- Political aspects -- United States; Official secrets -- United States; Religious fundamentalism -- Political aspects -- United States; United States -- Politics and government -- 2001-2009